Organization of Routine Immunization of The Population in Crisis Situations - Асадова Гульнара Акмаловна (Scientific Trends, 2023)
Immunization is one of the most effective methods of preventing and controlling infectious diseases. Routine immunization of the population is key to ensuring the health and well-being of people. However, in crisis situations, such as epidemics, wars or natural disasters, the organization of immunization becomes a more difficult task. In this article, we will look at how to organize routine immunization of the population in a crisis.
Keywords: immunization, crisis situations, population, planning, vaccination, healthcare, epidemic, pandemic, prevention, safety measures.